POSITONIC SOLUTIONS OF A VARIABLE-COEFFICIENT KdV EQUATION IN FLUID DYNAMICS AND PLASMA PHYSICS - GAO, YI-TIAN; TIAN, BO (International journal of modern physics. C, Computational physics, physical computation, 2001)
Positons are a new concept in nonlinear sciences. In this paper, we report some positonic, exact analytic solutions for a variable-coefficient Korteweg-de Vries (KdV) equation arising from fluid dynamics and plasma physics.